The Impact of Value Creation through Dynamic Capabilities on Competitive Advantage and Firm Performance - Zehir, Dr. Cemal; Allaham , Merve Vural (Migration Letters, 2024)
In the specific context of Turkey as a developing country, this study expands the existing literature by delving into the limited research on dynamic capability and value creation while incorporating dimensions of competitive advantage and firm performance. The objective of the study is to provide a comprehensive analysis of the role of dynamic capability in the value creation process. It particularly focuses on its impacts on competitive advantage and firm performance, and it aims to understand the mediating role of value creation. The study, emphasizing the dimensions of sensing, seizing, and transforming dynamic capabilities, centers on measuring their influence on functional, experiential, symbolic, and cost value types within the value creation process. With a sample size of 361, the research utilized quantitative data analysis and structural equation modeling through the Smart PLS software to test the research model. The findings reveal a positive impact of dynamic capability on the value creation process. Additionally, the study concludes that a company’s utilization of dynamic capabilities to create value for customers plays a mediating role in the relationship between competitive advantage and firm performance. These results emphasize the crucial role of dynamic capability in shaping sustainable competitive advantage and performance for businesses, especially in the context of a developing country like Turkey.